2022
DOI: 10.1111/jfpp.16751
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of vacuum drying and determination of functional properties of Kadam ( Neolamarckia cadamba ) fruit powder

Abstract: Kadam (Neolamarckia cadamba) is an under-utilized fruit found in South Asia. It is rich in minerals like iron and calcium (Pandey & Negi, 2017). The fruit has a short shelf life, and the taste is not appealing. The lack of post-harvest technology and its non-popularity has led to the fruit's underutilization. Dehydration is one of the oldest methods of food preservation used to reduce post-harvest losses (Chitrakar et al., 2018). Dehydrated fruits provide an excellent alternative to fresh fruits in the non-sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Subsequently, Šumić et al 25 dehydrated fresh red currants applying MRS and a Box–Behnken (BBD) experimental design. The optimized conditions for the response variables were established at a vacuum pressure 39 mbar, temperature 70.2 °C and drying time 8 h. Osama et al 26 used MRS to maximize vitamin C retention and minimize color degradation and a Box–Behnken design (BBD) was used for vacuum drying experiments. The results of the optimized process after applying MRS were established for the following factors: bed thickness 3.67 mm, vacuum pressure ~ 213.316 mbar, drying temperature 65 °C and blanching temperature 100 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Šumić et al 25 dehydrated fresh red currants applying MRS and a Box–Behnken (BBD) experimental design. The optimized conditions for the response variables were established at a vacuum pressure 39 mbar, temperature 70.2 °C and drying time 8 h. Osama et al 26 used MRS to maximize vitamin C retention and minimize color degradation and a Box–Behnken design (BBD) was used for vacuum drying experiments. The results of the optimized process after applying MRS were established for the following factors: bed thickness 3.67 mm, vacuum pressure ~ 213.316 mbar, drying temperature 65 °C and blanching temperature 100 °C.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, some studies have been done on the dehydration of kadam and its incorporation as functional ingredients in other food. 16,17 Osama et al, prepared cookies incorporated with kadam powder. They found that the incorporation of kadam in cookies decreased the hardness and resulted in dietary fiber and calcium enriched cookies.…”
Section: ■ Underutilized Cropsmentioning
confidence: 99%
“…The fruit is still considered underutilized due to its sour taste which causes a horripilation sensation, lack of research, and lack of technological advancement . However, some studies have been done on the dehydration of kadam and its incorporation as functional ingredients in other food. , Osama et al, prepared cookies incorporated with kadam powder. They found that the incorporation of kadam in cookies decreased the hardness and resulted in dietary fiber and calcium enriched cookies .…”
Section: Underutilized Cropsmentioning
confidence: 99%